Hubungan Karakteristik Wisatawan Milenial Indonesia Terhadap Pilihan Paket Wisata di Tugu Wisata Tour Travel Yogyakarta - Maiyati Eka Putri (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
This study entitled “The Relationship between the Characteristics of Indonesian Millennial Tourists and the Selection of Tour Packages at Tugu Wisata Tour Travel Yogyakarta”, aims to examine the relationship between the characteristics of millennial tourists and the selection of tour packages. This quantitative research investigates two variables: millennial traveler characteristics (X) and tour package selection (Y), using a sample of 80 respondents and data collected through questionnaires. Data analysis used simple linear regression using SPSS 25 and Pearson correlation test for hypothesis testing. The findings show a significant relationship, with a Pearson correlation coefficient (r) of 0.601, exceeding the critical value (tTable) of 0.220, leading to the rejection of Ho and acceptance of Ha. Future research could explore different variables or alternative case studies.